Weed Community Changes Due To Herbicide Treatment In Mature Oil Palm Plantations - Apriansa, Azharudin; Yakup, Yakup; Susilawati, Susilawati; Asmono, Dwi; Wandri, Ruli (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Stenochlaena palustris, commonly known as pakisan weed, poses significant challenges in oil palm plantations due to its highly invasive nature, which can lead to reduced agricultural productivity. Management of this weed is critical, as effective control measures can inhibit its dominance and promote the proliferation of alternative weed species, thereby enhancing biodiversity within the ecosystem. This study aimed to 1) assess the effectiveness of the herbicide ammonium glufosinate, in combination with an adjuvant, for controlling S. palustris in oil palm plantations, and 2) investigate the subsequent alterations in the weed community structure following herbicide application. We employed a randomised group design (RAK), incorporating the herbicide with added adjuvants. Results showed a clear change from S. palustris to Asystasia sp. as the dominant species. Treatments K and H had the most Asystasia sp., while treatment L had the least. Furthermore, we clearly compared treatments L, K, and S to the control treatment, emphasizing the emergence of diverse species within the treatment plots. However, low levels of diversity and evenness suggest a stressed weed community, indicating that the herbicide application can disrupt existing ecological balances. This study emphasizes the importance of assessing herbicide impacts not only on targeted weed species but also on broader community dynamics, revealing a significant research gap in understanding the long-term ecological consequences of herbicide use in oil palm plantations.